PEMANFAATAN KULIT BUAH NAGA DAN DAUN BAYAM SEBAGAI PEWARNA DALAM PEMBUATAN BATIK MOTIF VIRUS COVID-19 - Edi Suwasana; Ega Mawarni Putri; Aisyah Dewi Sri Annisa; Gabriella Krisnugtya Putri (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2021)
The times have demanded new innovations, including in the fields of culture and art. In accordance with this research, the process of making batik with motif inspiration from the form of the Covid-19 virus with natural dyes from dragon fruit skin and spinach is expected to be a new innovation in the art of batik. This study aims to determine how the process of making the covid-19 virus motif batik with natural dyes that have been determined. The method used in this research is the R&D method or in Indonesian it is called the research and development method. This experiment was carried out starting from December 1, 2020 at the AKS Ibu Kartini Batik laboratory, Semarang, which is located at Jl. Kawi No. 40 Kos Mas Gilang, Semarang city. In the experiment, the skin of dragon fruit was used as much as 500 gr and 300 ml of water, while spinach was 800 gr and 700 ml of water but the total for the dragon fruit was 7 kg and 4 liters of water & 2 kg of parrot with 1 liter of water, and the first and second immersion was carried out through several locks. The result of this research indicate that the design motifs designed are very suitable for tall thin people, the pink color produced from the dragon fruit skin and the brownish green color of the spinach are very suitable for prismatic cloth. While the locking which is suitable for the coloring of dragon fruit peel is locking alum and the dye from spinach is suitable for locking the gazebo.